(untitled) (Revista de Ensino em Artes, Moda e Design, 2026)
The Editorial Letter presents the Dossier Fashion, Extension, and Educational Management as the result of the maturation of the Working Group created at the Fashion Colloquium. The collected texts highlight university extension as a fundamental axis of education in fashion and design, articulated with critical and socially engaged pedagogical practices. The Dossier reaffirms the role of the university and of scientific events in the production of knowledge aligned with contemporary demands.